Enhancing thermal comfort and durability of foam concrete infill blocks through surface modifications - Nandakrishna R; Dhanya Sathyan; Athira R (Results in Engineering, 2025)
Foam concrete offers thermal insulation benefits for sustainable buildings but suffers from high shrinkage and permeability. This study explores surface modification using impermeable layers (40 MPa mortar, geopolymer) and coatings (polymer, water-based elastomer, nano waterproofing, epoxy) to improve mechanical, durability, and functional performance. Epoxy coating enhanced compressive and flexural strength by 69 % and 133.5 %, respectively. Geopolymer mortar improved compressive strength by 21.1 %, and 40 MPa mortar improved flexural strength by 41.1 %. Water-based elastomeric coating reduced water absorption by 64.2 % and sorptivity by 94.8 %. Epoxy showed the best acid resistance, with only a 24.3 % strength loss after 90 days. Thermal conductivity decreased from 0.09 to 0.06 W/m·K with nano and epoxy coatings. COMSOL thermal modeling showed an 8 °C indoor temperature reduction using epoxy-coated panels. This is the first comprehensive comparison of different surface treatments on foam concrete. Results demonstrate that epoxy and elastomeric coatings significantly enhance foam concrete’s durability and insulation, making it suitable for energy-efficient wall applications. The study offers a practical path toward more resilient, sustainable building materials.